“Heavenly Patterns” and Everyday Life in a Nutshell: Astronomy in Pre-Modern Chinese Handy Encyclopaedias - Bréard, Andrea (Writing the Heavens: Celestial Observation in Medieval and Early Modern Literature, 2025)
Complete Books of Myriad Treasures 萬寶全書 were an encyclopaedic genre popular in China from the seventeenth to early twentieth century. They showcased particularly useful classified knowledge claimed to dispense the readers from having to seek help from others in all matters of daily concern. These texts, comparable to a backscratcher1 so-to-say, provided in their very first chapter illustrations, memorization verses, and short texts on how to understand “heavenly patterns” (tianwen 天文) and eventually even exert influence on them through human action. These chapters covered a wide range of themes related to the sky: constellations, cosmogony, weather forecasting, uncommon celestial and meteorological phenomena interpreted as omens and other “heavenly patterns.” The chapter analyses how, through specific narrative and intertextual devices applied in these booklets, classical astronomical knowledge was reorganized in its relation to both enduring and extraordinary patterns of heaven, earth, and man, thus integrating the readers into cosmic theories. Given the high popularity of the Complete Books over three and a half centuries, my diachronic analysis of the transformations of the astronomical knowledge contained therein will also shed light on the resistance to “scientific” knowledge, not only transmitted since Antiquity but also brought to China during this time. The narrative is threefold. First, by giving agency to heaven as a writer (“When heaven is writing”), the term tianwen 天文was a concept understood as both a pattern in the sky and a written trace from heaven, a script that can be read and interpreted just like a text. In a second section (“Writing the heavens”), the chapter adopts the inverse perspective and looks at the Complete Books’ chapters on “heavenly patterns” and their “astronomical” content. The third section (“Re-writing the heavens”) describes the processes and modalities of writing the heavens in the Complete Books in terms of processes of recycling, exclusion, and recombination of readily available textual and visual material on “heavenly patterns